Sports Education and Athlete Character Building: Theoretical and Practical Perspectives - Nur Indah Atifah Anwar (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study analyzes the role of sports education in shaping athletes’ character through a literature review. It explores how physical education, sports training, and pedagogical approaches foster values such as sportsmanship, discipline, responsibility, teamwork, and integrity. The review examined fifteen peer-reviewed articles published between 2020 and 2025. Findings show that sports education, both in formal school settings and non-formal training environments, significantly contributes to athletes’ moral and mental development. Effective strategies include integrating religious and national values, applying sport psychology, and strengthening interpersonal communication between coaches and athletes. However, challenges such as competitive pressure, lack of synergy among educators, and limited policy support hinder comprehensive character-building efforts. Thus, stakeholder collaboration and capacity-building for sports educators are essential to establish a holistic sports education system that nurtures physically skilled, mentally resilient, and ethically grounded athletes.